Genome assembly of Vitis rotundifolia Michx. using third-generation sequencing (Oxford Nanopore Technologies) - M. M. Agakhanov; E. A. Grigoreva; E. K. Potokina; P. S. Ulianich; Y. V. Ukhatova (Труды по прикладной ботанике, генетике и селекции)
The immune North American grapevine species Vitis rotundifolia Michaux (subgen. Muscadinia Planch.) is regarded as a potential donor of disease resistance genes, withstanding such dangerous diseases of grapes as powdery and downy mildews. The cultivar ‘Dixie’ is the only representative of this species preserved ex situ in Russia: it is maintained by the N.I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR) in the orchards of its branch, Krymsk Experiment Breeding Station. Third-generation sequencing on the MinION platform was performed to obtain information on the primary structure of the cultivar’s genomic DNA, employing also the results of Illumina sequencing available in databases. A detailed description of the technique with modifications at various stages is presented, as it was used for grapevine genome sequencing and whole-genome sequence assembly. The modified technique included the main stages of the original protocol recommended by the MinION producer: 1) DNA extraction; 2) preparation of libraries for sequencing; 3) MinION sequencing and bioinformatic data processing; 4) de novo whole-genome sequence assembly using only MinION data or hybrid assembly (MinION+Illumina data); and 5) functional annotation of the whole-genome assembly. Stage 4 included not only de novo sequencing, but also the analysis of the available bioinformatic data, thus minimizing errors and increasing precision during the assembly of the studied genome. The DNA isolated from the leaves of cv. ‘Dixie’ was sequenced using two MinION flow cells (R9.4.1).